3403 Understanding the career pathways of scholars participating in Scholar Programs and Academy. (27th March 2019) - Patel, Tanha; Gesell, Sabina; Easterling, Doug
Abstract : OBJECTIVES/SPECIFIC AIMS: The Wake Forest Clinical and Translational Science Institute (CTSI) put in place a KL2 program in 2007 and introduced an 18-month Translational Research Academy (TRA) in 2010. The TRA provides education and leadership development training, research support services, mentoring, and networking opportunities to 15-20 early-career clinical and translational researchers, including those receiving KL2 awards. The KL2 and TRA programs make up the Mentored-Career Development Core that is administered by the Wake Forest CTSA Education Program. Over the years, the program administrators have collected feedback from the graduates on what they liked and did not like about the programs. However, a comprehensive evaluation to understand the impact of the trainings on helping scholars advance their research and their research careers was not conducted. The purpose of this evaluation was to assess if and how the KL2 and TRA programs are helping scholars advance their research and career in research. METHODS/STUDY POPULATION: Semi-structured phone interviews were conducted with 11 selected CTSI scholars from both KL2 and TRA programs. The interviews focused on 4 key areas: expectations coming into the program, role the program played in their career development over time, what else could/should have program done to support them and their research, and which of the other CTSI services were valuable in their career development. RESULTS/ANTICIPATED RESULTS: Even though scholars joined the program as an early-career researcher, the amount of experience in research they had varied and so did their areas of interest. The participants in the program also included both clinician and basic researchers. Scholars came into the program with different level of expectations and drive to use this program as a platform to lift their research careers. The conversations during these interviews gave an insight on career trajectories that the scholars have taken before and after joining the academy. For example, among the scholars that had graduated from the programs, 5 of the 6 had received a career development award, all 6 had their own grants to support their research, 3 had received professional promotions, and all 6 have an administrative leadership role they play, in addition to focusing on their research career. The information on where the scholars were at the beginning and the pathway they have taken to get to where they are now allowed us to better understand what aspects of the program was most valuable. The scholars noted that sessions around grant writing and developing specific aims were very helpful. Among the services provided, having a grant editor support was something that everyone noted as the most important service to them, even after leaving the program. DISCUSSION/SIGNIFICANCE OF IMPACT: The impact of the interviews and candid feedback provided by the scholars have been immensely valuable to program administrators to really understand the impact the program (and which components specifically) is having for the scholars. Looking at the career trajectories of the scholars, it was noted that scholars coming in to the academy with some experience doing research and ability to continue engaging in research benefited the most from what the program had to offer. Scholars that were still very early in their research career gained knowledge but were not always able to apply it because they were not working towards a grant at the time. Using the data on career trajectories, recommendations for improving the program, and other CTSI services that were most valuable, the program administrators decided to redesign the curriculum. The new version of the program is now tailored for scholars who have research experience and are working towards a career development grant such as a K or R. This will allow them to have a curriculum that is more intense and hands-on with an expectation that the scholars will submit the application towards the end of the program. A separate program is being developed for early-career researchers who are still setting their foot into t field to provide them basic research competencies through ad hoc courses and seminars.